Teaching College Probability for Higher Achievement - Irini Papaieronymou (Athens Institute for Education and Research, 2017)
This paper presents the results of a study which examined the role of particular tasks implemented through two instructional methods on college students' achievement in probability. A mixed methods design that utilized a pre-test (with multiple-choice items) and post-test (with multiple-choice and open-ended items) in treatment and control groups in an introductory statistics course was used. An analysis of pre-test scores indicated that students in the control and treatment groups had comparable initial probability knowledge. The results of the Wilcoxon Signed-Ranks test indicated that the multiple-choice scores of students in the control group were significantly lower on the post-test compared to the pre-test. In the case of the treatment group, student scores on the multiple-choice items did not increase significantly from the pre-test to the post-test. In addition, the results of the Mann-Whitney test showed that the normalized gain scores of the treatment group were significantly different from those of the control group. Relative to the open-ended post-test items, the Mann-Whitney test indicated that the scores of the treatment group on these items were significantly higher than the scores of the control group. Overall, the total post-test achievement of students in the treatment